Fetal Hydantoin Syndrome: A Case Report - Shakya, Needa Shrestha; Gurubacharya, Simmi Misra; Aryal, Dhana Raj (Journal of Nepal Paediatric Society, 2009)
A term baby born to an epileptic mother who was treated with Phenytoin until 10weeks of pregnancy was born with multiple congenital anomalies and diagnosed to have Fetal Hydantoin Syndrome. Infants of mothers who have taken hydantoin during pregnancy have been found to have broad multisystem patterns of abnormalities, including mental retardation, craniofacial anomalies, nail and digital hypoplasia and prenatal onset of growth deficiency. The discussion aims to bring to attention the potential hazard of the use of hydantoin drug during reproductive age to all medical practitioners. Key words: Congenital anomalies, epilepsy, fetal hydantoin syndrome, phenytoin. DOI: 10.3126/jnps.v30i1.2463 Journal of Nepal Paediatric Society Vol.30(1) 2010 57-59